Improving water deficit tolerance of Salvia officinalis L. using putrescine - Maryam Mohammadi-Cheraghabadi (Nature Portfolio, 2021)
Abstract To study the effects of foliar application of putrescine (distilled water (0), 0.75, 1.5, and 2.25 mM) and water deficit stress (20%, 40%, 60%, and 80% available soil water depletion (ASWD)) on the physiological, biochemical, and molecular attributes of Salvia officinalis L., a factorial experiment was performed in a completely randomized design with three replications in the growth chamber. The results of Real-Time quantitative polymerase chain reaction (qRT-PCR) analysis showed that putrescine concentration, irrigation regime, and the two-way interaction between irrigation regime and putrescine concentration significantly influenced cineole synthase (CS), sabinene synthase (SS), and bornyl diphosphate synthase (BPPS) relative expression. The highest concentration of 1,8-cineole, camphor, α-thujone, β-thujone, CS, SS, and BPPS were obtained in the irrigation regime of 80% ASWD with the application of 0.75 mM putrescine. There was high correlation between expression levels of the main monoterpenes synthase and the concentration of main monoterpenes. The observed correlation between the two enzyme activities of ascorbate peroxidase (APX) and catalase (CAT) strongly suggests they have coordinated action. On the other hand, the highest peroxidase (PO) and superoxide dismutase (SOD) concentrations were obtained with the application of 0.75 mM putrescine under the irrigation regime of 40% ASWD. Putrescine showed a significant increase in LAI and RWC under water deficit stress. There was an increasing trend in endogenous putrescine when putrescine concentration was increased in all irrigation regimes. Overall, the results suggest that putrescine may act directly as a stress-protecting compound and reduced H2O2 to moderate the capacity of the antioxidative system, maintain the membrane stability, and increase secondary metabolites under water deficit stress.